Vat photopolymerization-based 3D printing of complex-shaped and high-performance Al2O3 ceramic tool with chip-breaking grooves: Cutting performance and wear mechanism - Haidong Wu; Wei Liu; Yuerui Xu; Lifu Lin; Yehua Li; Shanghua Wu (Journal of Asian Ceramic Societies, 2023)
ABSTRACTDue to the processing of alumina ceramic cutting tools with complex shapes using traditional methods is difficult and time-consuming, vat-photopolymerization-based 3D printing was adopted to fabricate Al2O3 ceramic cutting tools with grooves for the first time. Subsequently, cutting performance evaluation and wear mechanism analysis were conducted. The relative density, Vickers hardness, and bending strength of the alumina cutting tools were determined. The effects of the cutting speed, feed rate, and cutting depth on the cutting performance and wear mechanism of the cutting tools were systematically investigated. In addition, two commercial cutting tools, namely cemented carbide and ceramic tools without grooves, were used for comparison. The cutting speed has the highest influence on the cutting performance, whereas the cutting depth has the least influence. The cutting performance of the prepared alumina cutting inserts with chip breaker grooves superior to that those without chip-breaking grooves and that of the cemented carbide tools. The wear mechanisms of the prepared alumina cutting tools and commercial tools were determined to be abrasive and adhesive wear, and those of the cemented carbide tools were adhesive wear and breakage. This work opens a new avenue for the future preparation of high-performance and complex-shaped ceramic cutting tools.